Perceptions of teachers, principals and school supervisors on students' skills using ICT in learning in the Senior High School - Rahmatina, Desi; Zaid, Norasykin Mohd (Universitas Malikussaleh, Aceh Utara, Indonesia, 2019)
This study examined on status of school (public and private school) differences for the perceptions of participats (teachers,principals and school supervisors ) in eleven senior high school on the students skills of Information and Communication Technology (ICT) in Tanjungpinang city, Kepulauan Riau Province,Indonesia. Data was taken by the use of online survey in 2016 who conducted by the Directorate General of Primary and Secondary Education of the Republic of Indonesia. We accumulate data from 310 respondents, they are 11 principals, 9 supervisors and 290 teachers on the eleven senior high school of Tanjungpinang district, Kepulauan Riau Province, Indonesia. Data analysis was done using quantitative analysis, the first using descriptive statistics mainly percentages perceptions of the principal, supervisor and teachers toward skill’s students using ICT in learning, the second to inferential statistical analysis of non parametric statistics Mann Whitney to test alternative hypothesis that there are significant difference skill’s students among public school and private school. SPSS software was used to analyze data.The results of the study shown that no different significantly on the students skill on use of computer in learning between public and private school (sig = 0.057), and there are different significantly on the students skill on use of mobile phone in learning between public and private school (sig = 0.001) and last result showed that there are different significantly on the students skill on use of internet in learning between public and private school (sig = 0.026).